Sovereign debt and human rights - Bantekas, Ilias; Lumina, Cephas (Oxford : Oxford University Press, 2019)
Sovereign debt is necessary for states to function, yet its impact on human rights is underexplored. Bantekas and Lumina gather experts to conclude that imposing structural adjustment programmes exacerbates debt, injures the entrenched rights of peoples and their state's economic sovereignty, and worsens the borrower's economic situation.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 8, 2019).
Keywords: Human rights -- Economic aspects; Debts, Public; Law; International law